Theoretical Foundations for the Development of Media Literacy of Students under the International Pisa Assessment Program - Uktamjonovich, Mirzaev Akramjon (International Journal on Integrated Education, 2023)
This article analyzes the theoretical foundations for the development of media literacy among students in the framework of the PISA international assessment program. The proposals and reasoning on the development of media literacy among students in the framework of the PISA international assessment program in the digital world are highlighted. Corresponding examples from foreign experience are given.